WESITE PENYEDIAN INFORMASI RUMAH KOS KAB.INHIL Studi Kasus: Sebagian Rumah Kos Yang Ada Di Tembilahan - Bayu Rianto (JUTI UNISI, 2019)
In connection with the development of information technology, naturally it will force the public to utilize the technology to the maximum extent possible from all aspects of life. Of course information varies, one of which is for students and students who will go to college or study in a place far from where they live. For this reason, it is clear at this time that students and students must immediately find a temporary residence to be used as their residence until the study is complete. The need for proper education has increased rapidly or significantly. Being aware of this, the author, builds a website-based boarding house information system, as a means of providing effective housing information for boarders, tenants, and managers Kons house to promote boarding houses that will be rented and manage everything related to boarding houses on the website quickly, easily, and up to date. Boarding house is a flat or single house that was built with the aim of being rented with a period of less than a month or annually or more. Website development uses the waterfall method, whereas for modeling using UML (unifield modeling language). The modeling languages ​​used are PHP and XAMPP for databases. Website Keb.Inhil Boarding House Information Provision is complemented by booking rented houses online to facilitate prospective boarding-dwellers without having to go straight to the field to order a boarding house.